Critical epistemology of the administration - López Mas, Johans Julio (2017)
This document is part of the currents of thought which recommended to deepen the epistemological foundations of current scientific disciplines. Its objective is to propose a vision on the epistemology of the administrative science, designed from the contributions of the critical epistemologies to modernity, guiding the research from the objectualization towards the situationality, rescuing the thought of Peter Drucker in his work, The Post-capitalist Society, (2004), which emphasizes that in today’s modern world dominated by organizations and the Administration, and, therefore, it is necessary to manage it properly. In our epistemological criticism of administrative knowledge we propose the search of an administrative paradigm(s) situated knowledge and a based on a cognitive relationship subject-subject that best explain our reality, our conflicts, paradoxes, challenges and challenges, and that involves the success of our organizations to the well-being of society.